Migration, Landscape Dynamics, and Fishermen Livelihood: A Case Study At East Kalimantan - Setiadi Setiadi (Indonesian Journal of Geography, 2020)
This paper argues for the interrelationship between migration process, dynamics of landscape structure, and sustainable livelihood based on an in-depth study in East Kalimantan, known as a hub of oil and gas and mining industry as well as plantation and housing area for fishing communities. Using anthropological approach, data was collected using a range of methods including observation, GIS-based spatial mapping, household survey, focus group discussion (FGD), and in-depth interviews.Findings of this study showed that the long process of landscape change has affected community livelihood due to differential resource allocation. Intensive migration occurring alongside rapid industrialization has not only increased competition between different interest groups, but has also changed local spatial configuration. Nonetheless, findings also highlighted integration between differentinterest groups which has also influenced livelihood. Such process is a form of ‘smart’ response in showing community resilience and ability to share living space by minimizing conflicts.